2005
DOI: 10.1677/jme.1.01784
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oestradiol and tamoxifen on oestrogen receptors-α and -β protein degradation and non-genomic signalling pathways in uterine and breast carcinoma cells

Abstract: Tamoxifen acts as an oestrogen antagonist in the breast reducing cell proliferation, but in the uterus as an oestrogen agonist resulting in increased cell proliferation. Tamoxifen exerts its tissue-specific effects through the oestrogen receptors (ER or ER ). The levels and functions of the two ERs affect the response of the target tissue to oestrogen and tamoxifen. We examined the control of ER stability in breast and uterine cell lines using western blotting and RT-PCR. In MCF-7 breast-derived cells, ER and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The negative cell cycle regulator cyclin G2 (CCNG2), which was recently identified as a primary ER target gene in MCF-7 breast cancer cells where it was robustly down-regulated by oestrogen but not OHT (Stossi et al 2006), was downregulated by both OHT and E 2 in Ishikawa cells demonstrating a further clear difference in response between breast and endometrial cells. We have previously shown that OHT is capable of stabilising ERa in Ishikawa cells, and inducing ligandmediated degradation of ERb protein, but not ERa (Horner-Glister et al 2005). This effect was shown to be cell-type specific, since in breast cancer cells, ERa protein is targeted for rapid degradation via the ubiquitin-proteasome pathway in response to E 2 (Dowsett & Ashworth 2003).…”
Section: Diverse Gene Expression Profiles Are Dictated or Influenced mentioning
confidence: 97%
See 2 more Smart Citations
“…The negative cell cycle regulator cyclin G2 (CCNG2), which was recently identified as a primary ER target gene in MCF-7 breast cancer cells where it was robustly down-regulated by oestrogen but not OHT (Stossi et al 2006), was downregulated by both OHT and E 2 in Ishikawa cells demonstrating a further clear difference in response between breast and endometrial cells. We have previously shown that OHT is capable of stabilising ERa in Ishikawa cells, and inducing ligandmediated degradation of ERb protein, but not ERa (Horner-Glister et al 2005). This effect was shown to be cell-type specific, since in breast cancer cells, ERa protein is targeted for rapid degradation via the ubiquitin-proteasome pathway in response to E 2 (Dowsett & Ashworth 2003).…”
Section: Diverse Gene Expression Profiles Are Dictated or Influenced mentioning
confidence: 97%
“…For all dosing experiments, the medium was replaced with RPMI 1640 containing 10% charcoal-stripped FCS (CSS, Hyclone) and 2 mM glutamine (Gmax) for 72 h prior to treatment with 10 K8 M 17b-oestradiol (E 2 ; Sigma), reported to significantly increase proliferation in MCF7 cells (Vanparys et al 2006), 10 K6 M (OHT; Sigma), which was shown to display both agonist and antagonist behaviour (Bramlett & Burris 2003) and induce proliferation (Horner-Glister et al 2005) …”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In podocytes isolated from diabetic mice treated with E 2 , neither ER copy number nor protein expression was regulated by treatment. We did, however, find an increase in ER protein expression without a change in ER mRNA copy number, suggesting a posttranslational regulation, such as protein stabilization [70,71]. As ER expression regulates apoptosis and cell cycle in breast cancer cells [72], the increase in the ER protein expression in podocytes could lead to cell cycle changes and increased cell survival, an effect which could protect against podocyte depletion in diabetic kidney injury.…”
Section: Of Podocyte Estrogen Receptors By Ementioning
confidence: 68%
“…[18][19][20] This can be partially explained by differences in the expression levels of ER, EGFR, and the HER-2 receptor. [21][22][23][24] Furthermore, it has been suggested that multiple mechanisms exist by which estrogen stimulation can lead to ERK activation.…”
Section: Introductionmentioning
confidence: 99%